STS Curriculum Development via Citizen Science on Coastal Plastic Waste - Quiao, Maria Alma D.; Balangiao, Ma. Vanessa O.; Dala, Khryssha Mae C.; Won, Maria Elma Q.; Barquilla, Manuel B. (Future Science / FSH-PH Publications, 2025)
In times of rapid change and persistent learner challenges, continuously updating curriculum materials is essential. The growing problem of plastic pollution stresses the need to integrate citizen science into education to ensure relevance, engagement, and contextual application. This study developed and evaluated a module-based curriculum material that embeds citizen science into the Science, Technology, and Society (STS) curriculum, focusing on the assessment of coastal plastic waste. An initial needs-assessment among STS instructors revealed strong agreement on developing localized, citizen-science-based materials to enhance environmental awareness. Quantitative findings demonstrated high acceptability from both experts and students. Expert evaluation yielded “Fully Acceptable” ratings in all categories, with visuals rated “Very Good (Acceptable)” (Mean = 3.67), indicating strong quality and minor areas for improvement. The Students’ Involvement Index (SII) of 1.07 reflected effective learner engagement, while the Fry Readability Graph placed the module at the college reading level. The Communication Index (CI) ranged from 0 to 0.01, with a CI of 0.01 indicating fair comprehensibility—acceptable but suggesting refinement of scientific terms. Qualitative feedback from students showed that the module was engaging, meaningful, and applicable to real-world issues. Overall, integrating citizen science into the STS curriculum proved to be a viable and impactful strategy for promoting environmental literacy, fostering active participation, and strengthening contextual understanding of coastal pollution among undergraduate learners. Future work should focus on improving visuals and clarity, expanding instructional resources, enhancing teacher training, and conducting broader and long-term implementations to strengthen its educational impact.